The Winning of the Partai Aceh in a Psychological Political Approach - Mukhrijal, Mukhrijal; Rassanjani, Saddam; Herizal, Herizal; Afrijal, Afrijal (Journal of Governance and Public Policy, 2021)
Partai Aceh is one of the local political parties in Aceh that able to win the first political contestation they participated in in 2009, even though it was born two years before in 2007. Since then, they have continued to dominate elections at the local level. Partai Aceh was established because of the peace agreement between GAM-RI as a post-conflict political agreement. The purpose of this study was to determine the victory of the Partai Aceh in the local realm. The method used is descriptive qualitative through interview techniques. The results of the study state that the Partai Aceh's victory in the context of Acehnese local politics cannot be separated from political psychology, such as the Partai Aceh identification approach through political socialisation, political candidates, and the Partai Aceh political campaign. The Partai Aceh approached the community involving the former Free Aceh Movement in conducting campaigns. The Partai Aceh's foresight in carrying the figure of a former GAM combatant impacted the Partai Aceh's victory.